2014
DOI: 10.1107/s1399004713030149
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the first small-molecule ligand of the neuronal receptor sortilin and structure determination of the receptor–ligand complex

Abstract: The identification of the first small-molecule ligand of the neuronal receptor sortilin and structure determination of the receptor–ligand complex are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
(41 reference statements)
1
23
0
2
Order By: Relevance
“…NT was found to bind within the tunnel of the b-propeller domain via its three C-terminal residues, YIL, 11 and we have recently shown that also small molecule inhibitors of NT binding occupies this YIL binding site. 12,13 Here we have set out to further study the structural properties of sortilin and the binding of NT using a broad biophysical approach. The data provided here suggest that NT is completely contained inside the tunnel of the b-propeller, firmly bound by its C-terminus in the previously reported binding site, and further attached by its N-terminal part at a low affinity site on the opposite side of the tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…NT was found to bind within the tunnel of the b-propeller domain via its three C-terminal residues, YIL, 11 and we have recently shown that also small molecule inhibitors of NT binding occupies this YIL binding site. 12,13 Here we have set out to further study the structural properties of sortilin and the binding of NT using a broad biophysical approach. The data provided here suggest that NT is completely contained inside the tunnel of the b-propeller, firmly bound by its C-terminus in the previously reported binding site, and further attached by its N-terminal part at a low affinity site on the opposite side of the tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…Neurotensin interacts with 3 neurotensin receptors (NTSRs): NTSR1, NTSR2, and NTSR3. Neurotensin-producing neurons are widespread in the brain and involved in several neuronal functions such as pain processing, blood pressure regulation, and food intake regulation (41). Outside the brain, neurotensin acts as a hormone with numerous endocrine and paracrine functions, such as regulation of intestinal motility, secretion of the pancreas, and tone of smooth vascular muscles (42).…”
Section: Neurotensin/ 177 Lu-3bp-227mentioning
confidence: 99%
“…Neurotensin interagiert mit 3 Neurotensinrezeptoren, NTSR1, NTSR2 und NTSR3. NTSR1 und NTSR2 sind G-Protein gekoppelte Rezeptoren, die an der Zelloberfläche exprimiert sind, während NTSR3 zur Gruppe der "vacuolar protein sorting 10 protein" (Vps10 p)-Rezeptoren gehört, die eine wichtige Rolle im intrazellulären Transport verschiedener Proteine spielt [42].…”
Section: Neurotensin/ 177 Lu-3bp-227unclassified
“…Neurotensin und Neurotensinrezeptoren sind deshalb an einer ganzen Reihe neuronaler Funktionen wie Schmerzverarbeitung, Blutdruckregulation und Regulation der Nahrungsaufnahme beteiligt. Auch in der Pathophysiologie verschiedener neurologischer und psychiatrischer Erkrankungen wie Schizophrenie, M. Parkinson und Drogenabhängigkeit ist das Neurotensin-System involviert [42].…”
Section: Neurotensin/ 177 Lu-3bp-227unclassified